Living in the Fake Faith - Li, Lu, 1992- (2020)
"Living in the Fake Faith" is an ongoing project which hopes to create scenes through fake faith（different media）to challenge time restriction, space separation, identity conflict, and lack of companionship. In the final project, I tried to live in Iceland with fake faith. The project's original idea comes from the 8-hour jet lag that occurred when I moved from China to Iceland. Due to jet lag and space separation, I must find special moments to communicate with people living in China by the Internet. I often say good morning to the people living in china when I prepare to sleep at night in Iceland and say good night when I after class. Jet lag can be seen as a fuse that led to time restriction, space separation, identity conflict, and lack of companionship. As more and more virtual reality technologies appear in our lives, the boundary between reality and virtual reality begins to blur. Can the development of future technologies and media be able to eliminate the time restriction, space separation, identity conflict, and lack of companionship brought by artificial rules? How do our next living spaces become better when it has more time restriction, space separation, identity conflict, and lack of companionship? Could we heal the time restriction, space separation, identity conflict, and lack of companionship?